Premenstrual syndrome in university students: its correlation with their attitudes toward gender roles. (3rd July 2018) - Temel, Safiye; Terzioglu, Fusun; Isik Koc, Gulten
Abstract: Introduction: Psychosocial factors causing premenstrual syndrome (PMS) are closely correlated with gender. Thus, this study's aim was to identify correlations between gender role attitudes (GRA) and PMS status of university students. Methods: The participants of this descriptive study were 1515 female students from 13 departments of Hacettepe University using stratified sampling method. Data were collected between February and May 2014 using a semi-structured questionnaire, the Premenstrual Syndrome Scale (PMSS), and the Gender Roles Attitude Scale (GRAS). Correlations between PMSS and GRAS scores were analyzed using the Spearman correlation coefficient. The difference between PMSS and GRAS scores in terms of sociodemographic characteristics was analyzed using the t -test and one-way analysis of variance. Results: The mean total PMSS score was 117.96 ± 34.41, indicating moderate PMS levels. The total mean GRAS score was 162.71 ± 17.50, indicating an egalitarian GRA. As the gender roles in marriage of the participants became traditional, depressive thoughts and swelling became more common ( r s = −0.620, p < .05; r s = −0.560, p < .05). The educational level of the mothers and perceived economic status were sociodemographic factors affecting both GRA and PMS. Discussion: GRA and sociodemographic characteristics should be considered in healthcare services for PMS.